1993
DOI: 10.5006/1.3299206
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Acid Corrosion of Steel by Some S-Alkylisothiouronium Iodides

Abstract: Five selected S-alkylisothisothiouronium iodides have been studied as acid corrosion inhibitors at 30°C for steel in 0.5 M H 2 SO 4 using gasometry, mass loss, and direct current (DC) polarization techniques. All of the data reveal that the compounds act as inhibitors in the acid environments; furthermore, polarization curves show that the compounds act as mixed-type inhibitors. It was found that the inhibition efficiency increases with the increase of the length of the additive alkyl chain. Langmuir's adsorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(67 citation statements)
references
References 18 publications
0
66
0
1
Order By: Relevance
“…Obviously, the E a with the presence of BTAOH is higher than that with the absence of BTAOH, which means the BTAOH molecules are physisorption on the mild steel surface. [39][40][41][42][43] Moreover, the adsorption enthalpy process (ÁH 0 ads ) was also estimated according to Eq. (6) 44,45 and the electrochemical parameters in Table 4.…”
Section: Adsorption Considerationsmentioning
confidence: 99%
“…Obviously, the E a with the presence of BTAOH is higher than that with the absence of BTAOH, which means the BTAOH molecules are physisorption on the mild steel surface. [39][40][41][42][43] Moreover, the adsorption enthalpy process (ÁH 0 ads ) was also estimated according to Eq. (6) 44,45 and the electrochemical parameters in Table 4.…”
Section: Adsorption Considerationsmentioning
confidence: 99%
“…The most well-known acid inhibitors are organic compounds containing nitrogen, phosphor, sulfur, and oxygen atoms. The surfactant inhibitors have many advantages such as high inhibition efficiency (IE), low price, low toxicity, and easy production [3][4][5]. The interactions between the inhibitor molecules and the metal surfaces should by all means be explained and understood in detail.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption of a surfactant markedly changes the corrosion resisting property of a metal. For these reasons, studying the relation between adsorption and corrosion inhibition is significantly important [14][15][16][17][18][19][20][21][22][23]. Somewhat recently, the corresponding research has also demonstrated that quaternary ammonium salt surfactants are efficient corrosion inhibitors for iron and steel [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%